Efficacy and safety of fospropofol disodium sedation for same-day bidirectional endoscopy in elderly patients: protocol for a prospective, single-center, randomized, double-blind, non-inferiority trial - Zhao, Zhe; Jin, Xiaogao; Li, Yong; Wang, Xiaofeng; Cui, Yongchen; Zhang, Bing; Kang, Yu; Zhang, Guangming; Chu, Qinjun; Zhang, Junfeng (Frontiers in Pharmacology, 2024)
Introduction: Fospropofol disodium is a novel prodrug that has improved pharmacokinetic and pharmacodynamic properties when compared with propofol. This trial aims to compare the efficacy and safety of fospropofol versus propofol sedation for same-day bidirectional endoscopy in elderly patients.This is a prospective, single-center, double-blind, randomized, propofolcontrolled, non-inferiority trial. A total of 256 adult patients aged 65 years or older, who are scheduled for same-day bidirectional endoscopy under sedation, will be randomly allocated, in a 1:1 ratio, to aeither fospropofol group or a propofol group (n=128 in each group). All patients will receive analgesic pre-treatment with sufentanil 5 μg. Two minutes later, an initial bolus dose of fospropofol 6.5 mg/kg or 1.5 mg/kg propofol and supplemental doses of fospropofol 1.6 mg/kg or 0.5 mg/kg propofol will be titrated as needed to achieve target sedation levels during the procedures.The primary outcome is the success rate of same-day bidirectional endoscopy. Secondary outcomes include the time to successful induction of sedation, duration, time to being fully alert, time to patient discharge, endoscopist satisfaction, patient satisfaction, and the top-up frequency and dosage of sedative medications. The safety endpoints consist of adverse events (AEs) concerning cough reflex, gag reflexes, body movement, muscular tremor, and pain on injection. Sedation-related AEs, including episodes of desaturation, severe desaturation (SpO2 < 90%), hypotension, severe hypotension (decrease in MBP ≥30% of baseline), and bradycardia, will also be recorded. Data will be analyzed on an intention-to-treat basis.Discussion: We hypothesize that the efficacy and safety of fospropofol sedation for elderly patients undergoing same-visit bidirectional endoscopy will not be inferior to that of propofol. Our findings will potentially provide a newdaily practice of sedation regimen for same-visit bidirectional endoscopy in elderly patients.